Pengembangan dan validasi instrumen body dysmorphic disorder mahasiswa - Nur Azizi Amrizon; Ifdil Ifdil; Yuda Syahputra; Rima Pratiwi Fadli; Nilma Zola; Yola Eka Putri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Tubuh yang